Highlights of the Society for Cardiovascular Magnetic Resonance 2025 conference: Leading the way to accessible, efficient, and sustainable cardiovascular magnetic resonance - Claudia Prieto; Bradley D. Allen; Clerio F. Azevedo; Bruno Bezerra Lima; Christopher Z. Lam; Rebecca Mills; Merel Huisman; Ricardo A. Gonzales; Sebastian Weingärtner; Anthony G. Christodoulou; Carlos Rochitte; Michael Markl (Journal of Cardiovascular Magnetic Resonance, 2025)
ABSTRACT: The 28th Annual Scientific Sessions of the Society for Cardiovascular Magnetic Resonance (SCMR) took place from January 29 to February 1, 2025, in Washington, D.C. SCMR 2025 brought together a diverse group of 1714 cardiologists, radiologists, scientists, and technologists from more than 80 countries to discuss emerging trends and the latest developments in cardiovascular magnetic resonance (CMR). The conference centered on the theme ''Leading the Way to Accessible, Sustainable, and Efficient CMR,'' highlighting innovations aimed at making CMR more clinically efficient, widely accessible, and environmentally sustainable.The program featured 728 abstracts and case presentations with an acceptance rate of 86% (728/849), including early career award abstracts, oral abstracts, oral cases and rapid-fire sessions, covering a broad range of CMR topics. It also offered engaging invited lectures across eight main parallel tracks and included four plenary sessions, two gold medalists, and one keynote speaker, with a total of 826 faculty participating. Focused sessions on accessibility, efficiency, and sustainability provided a platform for discussing current challenges and exploring future directions, while the newly introduced CMR Innovations Track showcased innovative session formats and fostered greater collaboration between researchers, clinicians, and industry. For the first time, SCMR 2025 also offered the opportunity for attendees to obtain CMR Level 1 Training Verification, integrated into the program. Additionally, expert case reading sessions and hands-on interactive workshops allowed participants to engage with real-world clinical scenarios and deepen their understanding through practical experience.Key highlights included plenary sessions on a variety of important topics, such as expanding boundaries, health equity, women’s cardiovascular disease and a patient-clinician testimonial that emphasized the profound value of patient-centered research and collaboration. The scientific sessions covered a wide range of topics, from clinical applications in cardiomyopathies, congenital heart disease, and vascular imaging to women’s heart health and environmental sustainability. Technical topics included novel reconstruction, motion correction, quantitative CMR, contrast agents, novel field strengths, and artificial intelligence applications, among many others.This paper summarizes the key themes and discussions from SCMR 2025, highlighting the collaborative efforts that are driving the future of CMR and underscoring the Society’s unwavering commitment to research, education, and clinical excellence.